PERLINDUNGAN KORBAN TRANSPLANTASI ORGAN TUBUH MANUSIA SECARA ILEGAL DARI PERSPEKTIF HUKUM HAK ASASI MANUSIA INTERNASIONAL - Nyoman Mas Gita Sawitri; Putu Tuni Cakabawa Landra; I Gede Pasek Eka Wisanjaya (Kertha Negara : Journal Ilmu Hukum, 2013)
The current development of medical science brings major advancements to world health today. These advancements can raise life expectancy of the patient. One of the advancement is in the field of organ transplantation. From a legal standpoint, organ transplantation and cells of the body are seen as something should be appreciated because it becomes action which helps the health of other people. The problem about the victim of illegal organ transplantation is actually not a new problem. That problem arose because several certain things that have been less attention or even ignored. The emergence of the term human rights is something related to a product of history. The term of human rights was originally a human desire and determination to be recognized and protected. Therefore, in this paper the protection to the victims of the illegal transplantation is discussed from the perspective of international human rights law. It also discusses the obstacles encountered in the protection of organ transplantation victims related to human rights.